Bioleaching of Copper-Containing Electroplating Sludge. (1st May 2021) - Sun, Jianxing; Zhou, Wenbo; Zhang, Lijuan; Cheng, Haina; Wang, Yuguang; Tang, Ruichang; Zhou, Hongbo
Abstract: The recovery of precious metals from solid waste through bioleaching has become a research hotspot in recent years. Thus, in this study, different strategies, such as chemical sulfuric acid leaching and mixed consortium bioleaching, were adopted to extract copper from Copper-Containing Electroplating Sludge. The results showed that, compared to chemical leaching, bioleaching showed a much better performance. Indeed, copper bioleaching efficiency reached 94.3% on day 7 (21.1% higher than that of chemical leaching). The results also indicated that the process of bioleaching involved more mechanisms and reactions than that of chemical leaching. The SEM and EDX tests showed that the surface morphology of the sludge changed significantly after bioleaching, and that an insignificant amount of copper remained in the leached residues. Furthermore, the leached residues passed the characteristic leaching toxic test and thus can be considered as non-hazardous raw materials for the construction industry. Hence, adopting a mixed consortium leaching process to extract copper from Copper-Containing Electroplating Sludge will not only significantly reduce environmental pollution, but will also use metal resources more efficiently. Graphical abstract: Image 1 Highlights: Different strategies were used to extract copper from CCES. Bioleaching had a much better performance than that of sulfuric acid. Bioleaching process involved more reactions than leaching with sulfuric acid. Bioleached residue could therefore be considered as non-hazardous material. Bioleaching from electroplating sludge proved to be efficient for Cu recycling.